Retroequatorial myopexy in the management of adult-onset cyclic esotropia - Saluja, Gunjan (Indian J Ophthalmol, 2020)
A 65-year-old otherwise healthy female, with bilateral normal visual acuity, presented with a unique pattern of strabismus. She complained of esotropia and diplopia occurring after every 24 h. There was no history of previous injury or ocular surgery. Other differentials were ruled out and the patient was diagnosed as adult-onset cyclic esotropia. The patient underwent right eye medial rectus retroequatorial myopexy, which tackled both diplopia and strabismus, without causing exotropia on nonsquint days.